THE IMPLEMENTATION OF PEER ASSESSMENT IN TEACHING SPEAKING OF MONOLOGUE - Dwi Eka Lestari (Journal of English Education Program (JEEP), 2015)
This study investigates the implementation of peer assessment in teaching speaking of monologue. According to Berg et al. (2006, p. 19), “peer assessment is a process in which students assess the quality of their students’ work and provide each other feedback”. The purpose of this study to investigate: (1) How the teacher implements peer assessment in teaching speaking of monologue? (2) Why the teacher implements peer assessment in teaching speaking of monologue? (3) Students’ perceptions on the implementation of peer assessment in teaching speaking of monologue?. To obtain the data, the writer used three instruments: classroom observation, interview, and questionnaire. The sample of this study was one English teacher and one class of the eleventh grade consisting of 20 students. The result of this study showed that the use of peer assessment is effective to be implemented as a technique to improve students’ speaking ability. In conclusion, it is recommended that peer assessment can be implemented in learning speaking of monologue at the eleventh grade of Senior High School. Key words: peer assessment, teaching speaking